The Use of Quizizz Application Based on Game Based Learning Model in Cultivating Reading Interest of Fifth Grade Students of SD Negeri 13 Lolong - Dira Putri; Gingga Prananda; Yona Syaida Oktira; Nofriza Efendi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Reading interest is one of the main indicators that is very important in the learning process. This study aims to describe the perceptions of teachers and grade V students of SD Negeri 13 Lolong towards the use of quizizz applications based on game-based learning models in fostering reading interest and identifying obstacles estimated by teachers and grade V students of SD Negeri 13 Lolong related to the application of quizizz applications based on game-based learning models in fostering reading interest. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. The data validity verification technique uses source triangulation. Furthermore, data analysis is carried out in three stages, namely data reduction, data presentation, and conclusion drawing. The subjects of this study are school principals, teachers, and fifth grade students. The results of the study indicate that teachers and students view the quizizz application, which is based on game-based learning, positively because it is considered enjoyable, capable of making learning more interesting, and encouraging students to read, while also aligning with the objectives of classroom activities aimed at fostering students' reading interests. Additionally, the challenges faced include limitations in technological infrastructure at schools, such as laptops, projectors, and limited smartphone ownership among students, as well as the absence of training on the quizizz application and supporting facilities like classroom reading corners.